Pathogenic variants of the GNAS gene introduce an abnormal amino acid sequence in the β6 strand/α5 helix of Gsα, causing pseudohypoparathyroidism type 1A and pseudopseudohypoparathyroidism in two unrelated Japanese families - Yasuhisa Ohata; Haruna Kakimoto; Yuko Seki; Yasuki Ishihara; Yukako Nakano; Kenichi Yamamoto; Shinji Takeyari; Makoto Fujiwara; Taichi Kitaoka; Satoshi Takakuwa; Takuo Kubota; Keiichi Ozono (Bone Reports, 2022)
Pseudohypoparathyroidism 1A (PHP1A) and pseudopseudohypoparathyroidism (PPHP) are caused by loss-of-function variants of GNAS, which encodes Gsα. We present two unrelated Japanese families with PHP1A and PPHP harboring unreported pathogenic variants of GNAS (c.1141delG, p.Asp381Thrfs*23 and c.1117delC, p.Arg373Alafs*31). These variants introduce abnormal amino acids in the β6 strand/α5 helix of Gsα, which interact with G protein coupling receptor (GPCR). We conclude that these variants alter the association of Gsα with GPCR and cause PHP1A or PPHP.